2001
DOI: 10.3171/jns.2001.95.2.0268
|View full text |Cite
|
Sign up to set email alerts
|

Surgery on a saccular vertebral artery—posterior inferior cerebellar artery aneurysm via the transcondylar fossa (supracondylar transjugular tubercle) approach or the transcondylar approach: surgical results and indications for using two different lateral skull base approaches

Abstract: Both approaches offer excellent visualization and a wide working field, with ready access to the lesion. This remarkably reduces the risk of development of postoperative deficits. These approaches should be used properly; the transcondylar fossa approach is indicated for aneurysms located above the hypoglossal canal and the transcondylar approach is indicated for those located below it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 25 publications
0
52
0
5
Order By: Relevance
“…The condylar fossa superior to the posterior condylar canal, which is the posterior portion of the jugular tubercle, is drilled extradurally and removed with the canal in sight as an anatomic landmark (13)(14)(15)(16). The key point of our preferred approach is the bony removal along the canal anteriorly resulting in removing the posterior part of the jugular tubercle and the atlanto-occipital joint can be kept intact (13,15).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The condylar fossa superior to the posterior condylar canal, which is the posterior portion of the jugular tubercle, is drilled extradurally and removed with the canal in sight as an anatomic landmark (13)(14)(15)(16). The key point of our preferred approach is the bony removal along the canal anteriorly resulting in removing the posterior part of the jugular tubercle and the atlanto-occipital joint can be kept intact (13,15).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Matsushima et al (13) in 1996, first proposed the supracondylar transjugular approach, which can also be called the transcondylar fossa approach. They has applied this approach to surgery for VA-PICA aneurysm (15,16), microvascular decompression for glossopharyngeal neuralgia (14,15), and removal of intradural tumors around the jugular tubercle or the hypoglossal canal (9). Gilsbach et al (8) also reported the supracondylar approach as a minimally invasive extradural approach.…”
Section: Pitfalls Of the Approachmentioning
confidence: 99%
See 3 more Smart Citations